Click reaction-induced in situ nanoparticle aggregation for cancer imaging and treatment - Yun Yin; Xiaoyang Liu; Xuemei Li; Gaolin Liang (EngMedicine)
With their high drug-loading capacity and enhanced permeability and retention (EPR) effects, nanoparticles possess significant potential for the diagnosis and treatment of tumors. However, unlike active targeting, the complex tumor microenvironment influences the passive accumulation of nanoparticles in tumor areas. Hence, it is necessary to actively control the behavior of nanoparticles when they enter the tumor microenvironment. By utilizing biocompatible and efficient click reactions, the aggregation of nanoparticles at the tumor site can be controlled, thereby enhancing nanoparticle accumulation at the target location with improved imaging signals and enhanced tumor-inhibitory effects. Herein, we introduce and classify in situ nanoparticle aggregation for biomedical imaging and therapeutic applications induced by four types of common click reactions: copper-catalyzed azide–alkyne cycloaddition (CuAAC), strain-promoted azide–alkyne cycloaddition (SPAAC), click condensation between 2-cyanobenzothiazole (CBT) and cysteine (Cys), and inverse electron-demand Diels–Alder (iEDDA). Furthermore, we summarize the main strategies of these click reaction-based nanoparticle aggregation approaches. Finally, we discuss the advantages and disadvantages of click reaction-triggered aggregation and analyze future trends.